Facade, Dr. Bhau Daji Lad Museum - Ghosh, Ayan (2023)
On 1st November 1858, Queen Victoria was proclaimed Queen of India from the Town Hall steps. It was decided in a meeting of Mumbai citizens that the first public institution should be a museum to honor the new Queen, with the botanical gardens attached to it. Governor Sir Bartle Frere laid the foundation stone for the museum on 19th November 1862.